A CONSULTA POPULAR COMO ESTRATÉGIA DE PLANEJAMENTO PARA O DESENVOLVIMENTO SOCIOECONÔMICO REGIONAL NO RIO GRANDE DO SUL - SIENDENBERG, DIETER R.; SOUZA, JOSE D. S. D.; RI, MARLENE K. D.; SILVA, PALOMA Z. D.; ALLEBRANDT, SÉRGIO L. (Salão do Conhecimento, 2013)
Resumo